2019
DOI: 10.3389/fnins.2019.01151
|View full text |Cite
|
Sign up to set email alerts
|

BAF45D Downregulation in Spinal Cord Ependymal Cells Following Spinal Cord Injury in Adult Rats and Its Potential Role in the Development of Neuronal Lesions

Abstract: The endogenous spinal cord ependymal cells (SCECs), which form the central canal (CC), are critically involved in proliferation, differentiation and migration after spinal cord injury (SCI) and represents a repair cell source in treating SCI. Previously, we reported that BAF45D is expressed in the SCECs and the spinal cord neurons in adult mice and knockdown of BAF45D fail to induce expression of PAX6, a neurogenic fate determinant, during early neural differentiation of human embryonic stem cells. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…H9 cells induced under Matrigel matrix gel-coated conditions downregulated OCT4 and expressed PAX6, NESTIN, SOX1 and other NSC markers. WNT25 and SHH are potent mitogens in the developing spinal cord [25]. After neural induction, we continued to inhibit SMAD and antagonize SHH and successfully obtained spinal cord NSCs with HOX-C protein family positivity.…”
Section: Discussionmentioning
confidence: 99%
“…H9 cells induced under Matrigel matrix gel-coated conditions downregulated OCT4 and expressed PAX6, NESTIN, SOX1 and other NSC markers. WNT25 and SHH are potent mitogens in the developing spinal cord [25]. After neural induction, we continued to inhibit SMAD and antagonize SHH and successfully obtained spinal cord NSCs with HOX-C protein family positivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that postmitotic neurons express BAF45B/C protein but lack the paralogous BAF45A/D, which confers neuronal properties[ 25 - 27 , 41 ]. The protein expression of BAF45D in adult rat NSPCs and neurons but not astrocytes may imply a role for BAF45D in the differentiation of NSPCs[ 44 ].…”
Section: Baf Complex Subunits and Their Main Characteristics In Nspcsmentioning
confidence: 99%
“…In the spinal cord, BAF45D is expressed in SCECs, neurons and oligodendrocytes, but not in astrocytes. After SCI, the expression of BAF45D in SCECs is decreased, and thus, proliferating SCECs mainly differentiate into astrocytes instead of neurons [ 50 ]. Therefore, the targeting of this peptide may be another potential way to affect neurogenesis after an SCI.…”
Section: Approaches To Promote Neurogenesismentioning
confidence: 99%